(untitled) (Iraqi Journal of Civil Engineering, 2017)
In this study an investigation of castellated beam are presented. The experimental and analytical results of seven simple castellated beams and other one has webbed section are summarized in this study. The target of the search was to study the structural behavior and mode of failure of castellated beams which have different geometric shape of hole and varies lengths span of beams, and attempt to find out the possibility of Biodgett equation and Halleux equation to determine ultimate and limit load respectively. Four angle off cutting were used to achieve the change in the geometry of hole (45, 50, 60 and 90 degree). The specimens were made from IB 203x133x25 and were expanded to 1.5 times the standard depth. Ultimate and limit load, load-deflection relation shapes and mode of failure were presented and discussed. The experimental results showed that the ultimate and limit load of castellated beams decreases with increasing the angle of cutting and Biodgett equation gives acceptable results for estimating ultimate load when the angle of cutting 50° or less. Also it is found that the limit load of castellated beam by Haleux equation is incorrect when the angle of cutting greater than 50°. As well as ANSYS-12 was used to analysis these beams by nonlinear finite element method. Four- nodes shell element (SHELL 181) was used to represent the castellated and webbed beams. This model was validated by comparison of the experimental and numerical results of ultimate load and their corresponding modes of failure.